Avalia????o da contribui????o do design thinking para a redu????o de incertezas em projeto - Feola, Jo??o Luiz de Mello Tavares (2016)
Business organizations and their projects are becoming increasingly complex and demanding constants innovations, looking to comply with an increasingly demanding and knowledgeable market need. In many cases, these innovative projects do not have welldefined requirements in the initial planning and need refinement scope in the execution course, which could disrupt the final project acceptance and quickly decision making. Uncertainties are a major cause of rework, cost increases and project deadlines changes. In extreme cases, they can even generate social and financial impacts. For this, it is necessary a dynamic and iterative approach between the team and the project stakeholders, which must abandon systemic management standards and pass thought in the customer problems and needs. The Design Thinking proposes a concept of collaborative work among stakeholders and project team, developing prototypes which are refined cyclically to its final stage and have shown to be a promising approach in education and engineering areas. This study aims to identify the DT characteristics and the corporate and its projects uncertainties types, checking also how it can help reduced. For this evaluation, we carried out qualitative interviews with nine experts, mostly professionals with graduate, active on seven different organizations. The analysis indicated that the majority DT approach has as predominates characteristics the involvement and relationship with the human being, tends to develop the creative thinking and use brainstorming techniques and customer feedback to develop their projects, increasing project acceptance and contractors satisfaction.